2003
DOI: 10.1074/jbc.m307202200
|View full text |Cite
|
Sign up to set email alerts
|

HER2/Neu- and TAK1-mediated Up-regulation of the Transforming Growth Factor β Inhibitor Smad7 via the ETS Protein ER81

Abstract: The cytokine transforming growth factor ␤ (TGF-␤) plays an important role in preventing tumor formation by blocking cell cycle progression. Accordingly, many cancers demonstrate mutations in TGF-␤ signaling components or enhanced expression of inhibitors of the TGF-␤ pathway such as Smad7. In this report we show that the oncoprotein HER2/Neu is able to collaborate with the ETS transcription factor ER81 to activate Smad7 transcription in breast, endometrial, and ovarian cancer cell lines. ER81 binds to two ETS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 72 publications
1
65
0
1
Order By: Relevance
“…We show that TGF-b is abundantly secreted in the peritoneal milieu through autocrine and paracrine mechanisms. The existence of a functional TGF-b signaling pathway in OC has been documented in prior studies (Cardillo et al, 1997;Baldwin et al, 2003;Dowdy et al, 2003), the cytokine and its receptors being expressed in over 50% of ovarian tumors (Bartlett et al, 1997;Bristow et al, 1999;Abendstein et al, 2000). Loss of growth inhibitory effects of TGF-b in OC cells has been attributed in a minority of cases to TGF-b receptor I and II inactivating mutations (Lynch et al, 1998;Chen et al, 2001) or to alterations of cell signaling downstream of SMADs Hu et al, 2000;Baldwin et al, 2003).…”
Section: Discussionmentioning
confidence: 60%
“…We show that TGF-b is abundantly secreted in the peritoneal milieu through autocrine and paracrine mechanisms. The existence of a functional TGF-b signaling pathway in OC has been documented in prior studies (Cardillo et al, 1997;Baldwin et al, 2003;Dowdy et al, 2003), the cytokine and its receptors being expressed in over 50% of ovarian tumors (Bartlett et al, 1997;Bristow et al, 1999;Abendstein et al, 2000). Loss of growth inhibitory effects of TGF-b in OC cells has been attributed in a minority of cases to TGF-b receptor I and II inactivating mutations (Lynch et al, 1998;Chen et al, 2001) or to alterations of cell signaling downstream of SMADs Hu et al, 2000;Baldwin et al, 2003).…”
Section: Discussionmentioning
confidence: 60%
“…Initial observations by Brodin et al (2000) indicated that TGF-b-induced Smad7 expression depends on cooperative interactions between AP-1, Sp1 and Smad proteins. More recently, both the JNK and TAK1/p38 pathways were shown to regulate Smad7 expression, in a cell-type-specific manner (Uchida et al, 2001;Dowdy et al, 2003). Also, ultraviolet irradiation, a know activator of MAPKs, activates Smad7 transcription in a c-Jun-dependent manner (Quan et al, 2005).…”
Section: Modulation Of Smad Activity By Mapksmentioning
confidence: 99%
“…Cells were seeded into 6-cm dishes that were coated with poly-L-lysine 12-24 h before transfection (30). Cells were then transiently transfected by the calcium phosphate coprecipitation method (31) and lysed 36 h after transfection with 50 mM Tris-HCl (pH 7.4), 150 mM NaCl, 50 mM NaF, 0.25 mM Na 3 VO 4 , 0.5% Igepal CA-630, 10 µg/ ml leupeptin, 2 µg/ml aprotinin, 1 µg/ml pepstatin A, 0.5 mM PMSF, 0.2 mM DTT. Immunoprecipitation was performed with anti-Flag M2 or anti-Myc 9E10 monoclonal antibodies as described (32).…”
Section: Introductionmentioning
confidence: 99%